Mediating epistemological access through asynchronous online discussion forums during the COVID-19 pandemic: Implications for re-imagining online collaborative self-directed peer engagement and learning - Moosa, R. (South African Journal of Higher Education, 2022)
The COVID-19 pandemic precipitated the burgeoning of online learning and asynchronous online discussion forums in higher education due to restrictions on face-to-face teaching and learning interactions. Previous research on asynchronous online discussion forums focused on the processes that enhance or limit discussion threads and how discussion posts develop students’ reflection and critical thinking skills. Although asynchronous online discussion forums are regarded as spaces for interactive learning, very little is known about how they facilitate epistemological access and enable collaborative peer learning interactions during periods of disruption such as the COVID-19 pandemic. The current study explores voluntary asynchronous online discussion forum participation in a non-credit bearing course from a unique angle of mediating epistemological access to online learning. This study draws on connectivist theory as a theoretical framework in a digital age where the student is in control of engagement interaction and information exchange. The central research question posed is how does an asynchronous online discussion forum mediate epistemological access to online learning and facilitate collaborative self-directed peer learning during the COVID-19 pandemic? The present study is underpinned by an inductive qualitative exploratory case study approach. A total of 2 146 discussion posts from 1 348 students across five faculties were downloaded from the learning management system and analysed using thematic analysis. This study indicates that epistemological access using a technology-mediated tool, is best facilitated through agency at the institutional, the instructor and the student level. The findings show that despite academic and technological challenges an online discussion forum enables epistemological access, interactive exchange of information and the formation of collaborative peer learning communities. In an age of digital inequalities, this study provides a starting point to uncover ontological barriers to epistemological access to online learning and signals the importance of integrating epistemological access, pedagogy and technology. This article concludes with implications for re-imagining the design of online multi-modal pedagogy to mediate online collaborative self-directed peer engagement and learning.